2019
DOI: 10.1074/jbc.ra118.004869
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate–oxaloacetate transaminase activity promotes palmitate lipotoxicity in rat hepatocytes by enhancing anaplerosis and citric acid cycle flux

Abstract: Edited by Jeffrey E. PessinHepatocyte lipotoxicity is characterized by aberrant mitochondrial metabolism, which predisposes cells to oxidative stress and apoptosis. Previously, we reported that translocation of calcium from the endoplasmic reticulum to mitochondria of palmitate-treated hepatocytes activates anaplerotic flux from glutamine to ␣-ketoglutarate (␣KG), which subsequently enters the citric acid cycle (CAC) for oxidation. We hypothesized that increased glutamine anaplerosis fuels elevations in CAC fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…In fact, added palmitate was not oxidized, since etomoxir, a CPT1 inhibitor which prevents uptake of the fatty acid into mitochondria [ 49 ], had no effects on OCRs or ECARs ( Fig S1 ). Cytosolic palmitate has previously been found to rewire the citric acid cycle and promote modified use of carbon sources [ 50 ], which is compatible with our results showing metabolic plasticity promoted by this fatty acid in the cytosol.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, added palmitate was not oxidized, since etomoxir, a CPT1 inhibitor which prevents uptake of the fatty acid into mitochondria [ 49 ], had no effects on OCRs or ECARs ( Fig S1 ). Cytosolic palmitate has previously been found to rewire the citric acid cycle and promote modified use of carbon sources [ 50 ], which is compatible with our results showing metabolic plasticity promoted by this fatty acid in the cytosol.…”
Section: Discussionsupporting
confidence: 92%
“…Li et al [75] suggested that the organism increased the metabolic rate to mitigate the stress condition. The liver in fish metabolizes the essential biomolecules and repair any physiological and biochemical disorder which include GOT and GPT activities [76]. The findings of the current study have showed increased GOT and GPT activity in O. niloticus which is presumed due to the alteration of the muscle and hepatic tissues.…”
Section: Plasma Enzymes Activitysupporting
confidence: 48%
“…The transfer of cytosolic NADH into mitochondria in cancer cells requires the MAS, which is composed of two antiporters, the malate-α-KG antiporter (SLC25A11 or OGC) and the glutamate-aspartate antiporter (SLC25A12 or aspartate-glutamate carrier isoform 1), as well as glutamic-oxaloacetic transaminase 1 and 2 (GOT1 and 2), and malate dehydrogenase 1 and 2 [ 22 , 29 ]. The MAS can be blocked by AOA, which inhibits GOT1 and 2 [ 30 ]. In this study, blocking MAS using AOA decreased OCR and ATP production by up to 90% in PDAC cells ( Figure 4 A), whereas it had no effect on OCR and ATP production in HPNE normal cells ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%